2018
DOI: 10.1016/j.ijnurstu.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating transition from children’s to adult services for young adults with life-limiting conditions (TASYL): Programme theory developed from a mixed methods realist evaluation

Abstract: Eight interventions were identified as facilitating transition from children's to adult services. The inter-relationships between these interventions supported two complementary models for successful transition. One focused on fostering a sense of confidence among adult service providers to manage the complex care of the young adult, and empowering providers to make the necessary preparations in terms of facilities and staff training. The other focused on the young adults, with service providers collaborating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(70 citation statements)
references
References 42 publications
0
69
0
Order By: Relevance
“…Hence, parents’ lack of attendance at adult clinic appointments may be a source of information discontinuity and have adverse effects on YAs’ condition management (Allen, Channon, Lowes, Atwell, & Lane, ; Lewis & Noyes, ). Interventions need to focus on collaboration between paediatric and adult services to develop an autonomous YA with the necessary self‐management skills while actively involving parents (Kerr, Price, Nicholl, & O'Halloran, ). Continued parental involvement with adolescents with diabetes is beneficial if there is gradual, supported and negotiated handover of responsibilities for self‐management (Byrne‐Davis, Salmon, Gravenhorst, Eden, & Young, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, parents’ lack of attendance at adult clinic appointments may be a source of information discontinuity and have adverse effects on YAs’ condition management (Allen, Channon, Lowes, Atwell, & Lane, ; Lewis & Noyes, ). Interventions need to focus on collaboration between paediatric and adult services to develop an autonomous YA with the necessary self‐management skills while actively involving parents (Kerr, Price, Nicholl, & O'Halloran, ). Continued parental involvement with adolescents with diabetes is beneficial if there is gradual, supported and negotiated handover of responsibilities for self‐management (Byrne‐Davis, Salmon, Gravenhorst, Eden, & Young, ).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the larger research study was to identify the factors associated with a successful transition from children's to adult services for young adults with life-limiting conditions (TASYL study) and used a mixed methods approach. The study had four phases of data collection, and the findings of the full research study are reported elsewhere [19]. Phase one involved the distribution of a survey questionnaire survey to health, social, education and nonstatutory organisations providing transition services to young adults with life-limiting conditions to identify current practices and is the focus of this paper.…”
Section: Methodsmentioning
confidence: 99%
“…Forbes et al [25] suggest the professional transition model which relates to the availability of a supportive individual, such as a transition coordinator, is particularly suitable for young adults with a shorter life expectancy. Despite this, the survey results indicate that, with the exception of the hospices, most organisations in the statutory health and social care sector were unlikely to take this approach even though it is well supported in the wider literature [19,26].…”
Section: Organisational Factors That Help or Hinder An Effective Tranmentioning
confidence: 96%
See 2 more Smart Citations